Research methods in early childhood : an introductory guide - Mukherji, Penny; Albon, Deborah (Los Angeles : SAGE, 2018)
The book covers the whole research journey exploring the different methodologies et principles as well as how to undertake a research project, making it a whole course companion. Following a linear and progressive structure, it logically helps students work through their course and introduces the topics to beginners in simple and clearly explained terms. Once students have gained confidence, they are able to delve into the further reading suggestions and the research in focus boxes which look at international published examples of research to understand the real world effects and implications. Activities throughout help cement knowledge and case studies giving examples and scenarios of real student research show readers how to present their own findings. A brand new reader guide to research to aid navigation and a new chapter on research proposals are now also included.
Includes bibliographical references and index.
Keywords: Preschool children -- Research -- Methodology; Lehrbuch; Lehrbuch